Application of VATS in Diagnosis and Treatment of Lung Cancer Complicated with Pneumothorax (Bioscience Journal, 2018)
The paper aims to explore clinical symptoms and complication characteristic of lung cancer complicated with pneumothorax, analyze clinical diagnostic value of VATS for the disease, and elaborate on specific clinical programs and significance. To investigate diagnosis and therapeutic value of VATS for lung cancer complicated with pneumothorax, 1900 cases of patients with lung cancer complicated with pneumothorax were randomly selected as research objects to be treated with VATS, and detailed analysis of their clinical data was done. The clinical data showed that pathology of many patients was not clearly diagnosed before operation. By VATS operation research, lung tumor tissue was removed during surgery to be Â received with frozen section. Appropriate surgical approach was chosen based on specific circumstances of patients. As can be known from the results, 1000 cases were treated with wedge resection of lung tumor under thoracoscopy, 900 cases were treated with assisted small incision surgery under thoracoscopy, and 1400 cases of lung metastasis were treated with pleural friction fixation. All the operations were successful, with pathology clearly diagnosed. After surgery, 8 patients had mild air leakage, which could heal without special treatment. There was no perioperative death. The above analysis shows that VATS can clearly diagnose peripheral lung tumor with great pathological inference significance, and fundamentally cure pneumothorax and lung cancer, which is thus recommended in clinic.